ANALISIS PENGARUH MINAT NASABAH DALAM MENGGUNAKAN MOBILE BANKING DENGAN MENGGUNAKAN KERANGKA TECHNOLOGY ACCEPTANCE MODEL (TAM) - Yosua Carunia Agung Nuwa; Teresia Perpetua Kota (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of Technology Acceptance Model (TAM) risk and service quality on customer interest in using mobile banking services.The method used in this study is a quantitative method with data collection through questionnaires distributed to respondents throughout Indonesia who use mobile banking services. Samples were taken as many as 285 respondents with accidental sampling technique. The data obtained was then processed using the amos.24 tool and using the IBM SPSS 25 . program Based on the results of the hypothesis, it shows that perceived benefits and perceptions of convenience have a positive and significant effect on customer interest in using mobile banking. Risk has a negative and significant effect on customer interest in using mobile banking services. Service quality has a positive and insignificant effect on customer interest in using mobile banking services.